Introduction to counseling and guidance - Gibson, Robert L.
The seventh edition of Gibson & Mitchell's Introduction to Counseling and Guid ance retains its logical progression of topics, while introducing the latest technologies, concepts, and applications in the counselor's repertoire. As they have in previous editions, the authors present practical examples and discussions of all of the major facets of counseling in a wide variety of counselors' work settings